Awareness and knowledge of autism spectrum disorder in Western China: Promoting early identification and intervention - Wei, Hua; Li, Yan; Zhang, Yu; Luo, Jinmei; Wang, Shuang; Dong, Qiujun; Tao, Yuanyuan; Gong, Ling; Feng, Yang; Shi, Mingmei; Cao, Zhenghui; Liu, Yongfang; et al. (Frontiers in Psychiatry, 2022)
Purpose Given the increasing prevalence of autism spectrum disorder (ASD) and the public health problems it creates; early identification and interventions are needed to improve the prognosis of ASD. Hence, this study surveyed different groups of people who are likely to have early contact with autistic children to provide an informed basis for early detection and effective diagnosis and interventions. Methods Three groups of people were recruited for the study from Changshou District and Wushan County of Chongqing, in Western China: 269 medical workers, 181 educators, and 188 community residents. Their understanding and knowledge of autism was measured using a self-made questionnaire. Results The positive finding was that the three groups had a certain level of understanding of autism, but they had some misunderstandings of the core problems, and there were significant differences in the understanding of autism among the three groups. Younger medical workers knew more about autism than older ones did. The ability of educators and community residents to identify autistic symptoms was positively related to their level of education and their experience with autistic children. Television and the internet were the main sources of information about autism for participants. Conclusions The medical workers, educators, and community residents in the investigated areas in western China may be able to identify early signs of autism but have an inadequate understanding of autism. In areas far from cities, it is necessary to strengthen the training of medical workers in primary health care to promote autism screening and referral in educational institutions and communities. Using internet technology to provide public education and professional training about autism in remote areas could be a very promising method in Western China.